2016
DOI: 10.1002/bab.1477
|View full text |Cite
|
Sign up to set email alerts
|

Jasmonic acid and methyl dihydrojasmonate enhance saponin biosynthesis as well as expression of functional genes in adventitious roots of Panax notoginseng F.H. Chen

Abstract: Panax notoginseng, an important herbal medicine, has wide uses for its bioactive compounds and health function. In this work, we compared the content of saponin in cultivation and adventitious root. The total content of saponins in adventitious root (8.48 mg⋅g ) was found lower than in the native one (3-year-old) (34.34 mg⋅g ). To enhance the content of bioactive compounds, we applied elicitors jasmonic acid (JA) and methyl dihydrojasmonate (MDJ) to the adventitious root culture. It was observed that the highe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 51 publications
(59 reference statements)
1
20
0
Order By: Relevance
“…Such observation further highlighted the combo action of in vitro adventitious root cultures, and JA elicitation can contribute towards understanding the gene expression pattern and biosynthesis of andrographolide and other DLs. Previous studies on elicitation and identification of gene regulation pattern for secondary metabolite production give credence to the present findings [59][60][61][62].…”
Section: Discussionsupporting
confidence: 87%
“…Such observation further highlighted the combo action of in vitro adventitious root cultures, and JA elicitation can contribute towards understanding the gene expression pattern and biosynthesis of andrographolide and other DLs. Previous studies on elicitation and identification of gene regulation pattern for secondary metabolite production give credence to the present findings [59][60][61][62].…”
Section: Discussionsupporting
confidence: 87%
“…The phytohormones JA (Li et al 2017) and auxin ( Figure 4F-J) are involved in the regulation of saponin biosynthesis. The concentrations of the phytohormones JA and IAA in P. notoginseng inoculated with D212 were further examined.…”
Section: Resultsmentioning
confidence: 99%
“…Saponins are the main medical components in P. notoginseng and have high clinical value, exhibiting antiinflammation, anti-oxidation, inhibition of platelet aggregation, regulation of blood glucose and blood pressure, inhibition of neuronal apoptosis, and neuronal protection (Xie et al 2018). The saponins are mainly biosynthesized in the roots of P. notoginseng and can be induced by JA (Li et al 2017) and auxin (Washida et al 2004). In addition, saponins with autotoxicity can cause replant failure of P. notoginseng (Yang et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that only Rb 3 was detected in the Aspergillus. niger treatment group (Li et al, ). HPLC‐ESI‐MS analysis and mass spectrometry spectra showed that the Panax japonicus var.…”
Section: Discussionmentioning
confidence: 99%